2019
DOI: 10.7759/cureus.4377
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Deep Surgical Site Infection Following Spinal Surgery: A Pilot Study

Abstract: Introduction Surgical site infection (SSI) is the most common healthcare-related infection in surgical patients. Patients who have undergone spinal surgeries and have contracted postoperative SSI face increased morbidity and mortality, which invariably leads to additional burden on the healthcare system and higher costs. The risk factors for the increase in SSI in patients who have undergone spinal surgery have been investigated in numerous studies but no studies have been performed in Malaysia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Heterogeneity was high ( I 2 = 58.9%), and a significant publication bias was found (Harbord’s p = 0.001). Subgroup meta-analysis of two studies analysing infection risk after elective spinal surgery 48 , 49 revealed a significant association between smoking and risk for postoperative infection (RR: 4.38; 95% CI: 2.17–8.85; p < 0.001; Fig. 3 ).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Heterogeneity was high ( I 2 = 58.9%), and a significant publication bias was found (Harbord’s p = 0.001). Subgroup meta-analysis of two studies analysing infection risk after elective spinal surgery 48 , 49 revealed a significant association between smoking and risk for postoperative infection (RR: 4.38; 95% CI: 2.17–8.85; p < 0.001; Fig. 3 ).…”
Section: Resultsmentioning
confidence: 96%
“…Three studies were prospective non-randomized cohort studies (14.3%; level III), 49 , 65 , 66 and 18 were retrospective studies (85.7%; level IV). 21 , 48 , 50 – 64 , 67 The overall RR for smokers to develop postoperative infections was 2.20 (95% CI: 1.69–2.86; p < 0.001; Fig. 3 ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…This was contradictory to studies that demonstrated these associations for other surgical procedures. [39][40][41] This is possibly caused by a lack of correction for other contributing factors in smokers, such as comorbidities or ASA score. Unlike those studies, most articles included in this meta-analysis for surgical site infection 17,33 and fistula formation 7,35 performed a multivariate analysis, correcting for contributing factors.…”
Section: Discussionmentioning
confidence: 99%